Analisis Penyebab Turnover Intention Karyawan Pada Perusahaan Dalam Novel Resign Karya Almira Bastari (International Forum of Researchers and Lecturers, 2024)
A good company is one that takes care of its employees. If employees feel uncomfortable working in the company, it can cause the risk of employee turnover intention in a company. A high turnover intention rate can hinder the achievement of company goals. Supriadi, Trang, and Rogi (2021:1217) explain that turnover intention is a situation where employees of an organization have plans to leave their jobs, or the tendency for employees to voluntarily stop working from their jobs according to their own choice. In the novel Resign by Almira Bastari tells the story of an employee who is tired of working from a company and wants to Resign from the company immediately. From the novel, the researcher aims to analyze the factors that cause the turniver intention of company employees in the novel using qualitative descriptive methods. Qualitative descriptive method is a research procedure that can produce descriptive data in the form of written or spoken words of people and behavior that has been observed (Moleong, 2018: 4). The results of the analysis that has been carried out by researchers found that there are 4 factors that cause turnover intention in the novel, namely workload, job satisfaction, unsupportive leadership style, and compensation. The conclusion of this study is that a company cannot run without employees, therefore to achieve the goals of the company, it is important for companies to pay attention to the condition of their employees so that employees can work as much as possible and reduce the risk of turnover intention in the company.